Visual Impairment and Eye Diseases in HIV-infected People in the Antiretroviral Therapy (ART) Era in Rakai, Uganda. (2nd January 2021) - E, Jian-Yu; Wang, Zhengfan; Ssekasanvu, Joseph; Munoz, Beatriz; West, Sheila; Ludigo, James; Gray, Ronald; Nakigozi, Gertrude; Kong, Xiangrong
ABSTRACT: Purpose: Antiretroviral therapy reduced infectious eye diseases (EDs) in HIV-infected people. There is limited data on age-related EDs and visual impairment (VI) in people living with HIV. We report prevalence of VI and spectrum of EDs in HIV-infected people in an ART era in Rakai, Uganda. Methods: A philanthropic campaign during 2009–2012 provided ophthalmic services to HIV+ patients in care. Unilateral presenting visual acuity (VA) was assessed by a trained staff in HIV clinics using a 6-m Snellen chart. A slit-lamp examination by an ophthalmologist evaluated eyes with impaired acuity. A retrospective chart review was later conducted retrieving data of patients participating the ophthalmic service. VI was defined referencing WHO's ICD-11. Ophthalmic diagnosis was summarized by VI level. Logistic regressions estimated demographic associations with cataract diagnosis. Results: 688 HIV+ patients were evaluated, median age was 44 (IQR: 37–50) years, 69% were female. Fifty-one percent were on ART (median duration 4, IQR: 2–5 years). Crude prevalence of moderate/severe VI and blindness were both 2%. The main diagnoses were refractive error (55%), conjunctivitis (18%), cataract (15%), and pterygium (11%). Cataract prevalences were 10%, 12%, and 26% among age groups of 19–34, 35–49, and ≥50 years, respectively. Cataract was found in 73% of the HIV+s with blindness and in 63% of those with moderate/severe VI. Older age and male sex were significantly associated with higher cataract prevalence. Conclusion: VI in HIV+ patients in Rakai was mainly due to refractive error and cataract. Cataract was common in all age groups.